Measuring Electrical Activity of the Brain: ERP Mapping in Alcohol Research - Chorlian, David B; Porjesz, Bernice; Cohen, Howard L (Alcohol Health and Research World, 1995)
The recording of brain electrical activity from scalp electrodes provides a noninvasive, sensitive measure of brain function. Event-related potentials (ERP's) are brain waves that are recorded while the subject is exposed to a specific sensory stimulus. Depending on experimental conditions, ERP's are useful in studying many brain functions, such as sensory and information processing (e.g., memory). The assessment of ERP's is useful in studying the effects of alcohol on brain function and in identifying people at risk for developing alcoholism. Computerized mapping techniques produce graphs or color-coded images to summarize data about the generation of ERP's in time and space.